1997
DOI: 10.1084/jem.185.2.367
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Binding Motifs Derived from Random Peptide Libraries Differ at the COOH Terminus from Those of Eluted Peptides

Abstract: Recombinant HLA-A2, HLA-B8, or HLA-B53 heavy chain produced in Escherichia coli was combined with recombinant β2-microglobulin (β2m) and a pool of randomly synthesised nonamer peptides. This mixture was allowed to refold to form stable major histocompatability complex (MHC) class I complexes, which were then purified by gel filtration chromatography. The peptides bound to the MHC class I molecules were subsequently eluted and sequenced as a pool. Peptide binding motifs for these three MHC class I molecules wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…In contrast, we observed several differences to HLA-peptidebinding studies [5] where Gly was found among the preferred amino acids at the C-terminus of the peptides: none of our 121 HLA-BÃ1801-presented ligands showed a Gly in PO. Such discrepancies between analysis of natural ligands and binding studies have already been reported [24]. Mere binding to a certain HLA molecule is not sufficient for natural presentation since critical steps of antigen processing other than HLA binding (such as proteolytic activities and specificities as well as transport preferences) do play a major role.…”
mentioning
confidence: 92%
“…In contrast, we observed several differences to HLA-peptidebinding studies [5] where Gly was found among the preferred amino acids at the C-terminus of the peptides: none of our 121 HLA-BÃ1801-presented ligands showed a Gly in PO. Such discrepancies between analysis of natural ligands and binding studies have already been reported [24]. Mere binding to a certain HLA molecule is not sufficient for natural presentation since critical steps of antigen processing other than HLA binding (such as proteolytic activities and specificities as well as transport preferences) do play a major role.…”
mentioning
confidence: 92%
“…We addressed this issue by generating recombinant soluble T18 d H chain molecules in E. coli and refolding this protein with ␤ 2 m in the presence or absence of a fully random nonameric peptide library containing all natural amino acids except Cys. This approach was successfully used to investigate the peptide binding motif of another class Ib molecule, Qa-1 (24), in addition to class Ia molecules (33,34). In Fig.…”
Section: T18 D Folds Efficiently With ␤ 2 M In the Absence Of Peptidementioning
confidence: 99%
“…BIMAS underestimated the activity of peptide GKLGFVFTL (experimental log T 1/2 : 3.176; BIMAS: 0.745; COMBINE: 2.778) and overestimated that of peptide GLGGGGFGV (experimental log T 1/2 : 0.903; BIMAS: 2.606; COMBINE: 1.651). For high activity (large log T 1/2 value in this study), the identity of the second amino acid residue of the HLA-A2 epitope peptide has been reported to have a Leu or an Ile residue [21][22][23]. Peptide GKLGFVFTL (see above) displays high activity even though its second residue is a Lys (K), a topology that does not meet the preference criteria mentioned above.…”
Section: Resultsmentioning
confidence: 99%